PENGARUH MODAL, JUMLAH TENAGA KERJA, DAN LAMA USAHA TERHADAP PENDAPATAN PANGKALAN GAS DI KECAMATAN TABANAN TAHUN 2022 - I NYOMAN GEDE MARTA (Universitas Mahasaraswati K. Mataram, 2023)
Tabanan sub-district has many small and medium entrepreneurs, one of their business fields, namely the entrepreneur of the LPG gas base. The aim of this study is to determine the effect of capital, number of workers and length of business partially and simultaneously on the income of LPG base entrepreneurs in Tabanan District, Tabanan Regency.This research was conducted on LPG gas base entrepreneurs in Tabanan District. The data analysis technique used in this study consisted of the classical assumption test and multiple linear regression analysis, multiple determination coefficient analysis, t-test and F-test.The results of the study show that capital (X1) has a positive and real influence on the income of LPG base entrepreneurs, because the t count is greater than t table and the significance is less than 5 percent. The number of workers has a positive and real influence on the income of the LPG base entrepreneur, and the significance is less than 5 percent. The length of business has a positive and real influence on the income of the LPG base entrepreneur, because the t count is greater than the t table and the significance is less than 5 percent. Based on the simultaneous test, F count is greater than F table, so the variable capital, number of workers and length of business simultaneously have a significant effect on the income of the LPG base entrepreneur in Tabanan District.